Peran LAZIZMU dalam Mengatasi Kemiskinan di Lingkungan Masyarakat: Studi Kasus LAZIZMU Sragen - Nasywa Safira Awwaliyyah; Muh Nur Rochim Maksum (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research examines the role of Lembaga Amil Zakat Infaq and Shadaqah Muhammadiyah (LAZIZMU) Sragen in efforts to overcome poverty in the community. Using a descriptive qualitative approach, this research aims to review more deeply the strategies and innovative programs implemented by LAZIZMU Sragen and their sustainable impact. The results showed that LAZIZMU Sragen has developed various structured programs, including MSME empowerment, education assistance, zakat education, and humanitarian assistance. These programs have provided positive impacts such as improved mustahiq economy, better access to education, and increased zakat awareness in the community. Collaboration with the government and other social institutions also allows LAZIZMU Sragen to reach more people in need. Nevertheless, LAZIZMU Sragen still faces challenges in zakat education, limited resources, and ensuring program sustainability. This study concludes that LAZIZMU Sragen's programs have significant sustainability potential in poverty alleviation, but continuous program evaluation and improvement are needed to maximize their long-term impact.